Meks Coffee / Muhammad Amirul Hussaini Rusni - Rusni, Muhammad Amirul Hussaini (2021)
Meks Coffee is a home-base business that sells drink using big plastic cup as their USP. The business started since 27th August 2019. Their target audience is teenagers and adults. But mainly teenagers often repeat order because how convenience it is to just Whatsapp the number and take the order just outside their house through COD method. The other main attraction is not just the size of the cup but also the value you get with the purchase. For only RM5 for each cup no matter you buy the basic menu or the mix special menu the price is still the same. Our business is conducted entirely through COD and whatsapp for now. But now we had start using Facebook as other method of marketing. We will upload all the items we have on the ‘Facebook Page’ and include the ‘details’ of the items in the ‘description’ space.